Experimental Work on Competence Building of a University Teacher in Inclusive Education by Means of Digital Technology - I.V. Vinokurova; I.F. Filchenkova (Moscow State University of Psychology and Education, 2023)
The article presents the results of experimental work on the formation of the competence of university teachers in inclusive education by means of information technology in additional professional education. Information technology is implemented on the basis of two components: information and technology. The didactic digital complex acts as an information component, the technological component provides the personification of the educational process, the use of a set of forms and methods of training for intensifying the process of additional professional education using information and communication technologies, creating conditions for the formation of pedagogical communities for the exchange of experience and interactive solving of the professional tasks in. 353 teachers from 6 educational universities were recruited for this study. The effectiveness of the study was confirmed by the method of mathematical statistics (Pearson's criterion).